Pengaruh Faktor Pendidikan, Konsumsi Protein, Konsumsi Kalori, dan Upah terhadap Indeks Pembangunan Manusia Bangsa Indonesia - Kiki Ismanti (Sosio e-Kons, 2017)
ABSTRACT This study is aimed to examine the effect of the relationship between education, protein consumption, calorie consumption, wages rate or income and human development index of Indonesia. The study uses data on the Human Development Index of Indonesia of 1994-2013. The object of this research is the discussion on the effect of the relationship of variables of education, protein consumption, calorie consumption, wages rate or income and the human development index. The researcher uses the survey method with the correlation technique as a method of sampling. In the data collection process, the researcher uses secondary data of 1994-2013, which are obtained from BPS-Statistics Indonesia by using documentation technique. The calculation result of final equation of estimation is ? = 45,992 + 0,215 X1 + -0,264 X2 + 4,156 X3 + 0,321 X4. The determinant coefficient is 98.9 percent, and the remaining 1.1 percent is affected by other variables. It means that the contribution of variables of education, protein consumption, calorie consumption, and wages rate or income on the human development index is 98.9 percent, and the remaining 1.1 percent is contributed from other independent variables outside of the research model. Based on the results of research, the minimum regression coefficient on the Human Development Index is a variable of protein consumption, which is only -0.264. Therefore, the Government of Indonesia is expected to formulate the policy that allows high accessibility of notorious foods, which contains adequate protein and calories for Indonesian people. Keywords: Education Factors, Nutrition, Calorie Consumption, Level of Wages, and Index of Quality of Life (IMH/HDI).ABSTRAKTujuan dalam penelitian ini adalah untuk mengetahui pengaruh hubungan antara pendidikan, konsumsi protein, konsumsi kalori, dan upah dengan indeks pembangunan manusia Indonesia. penelitian ini menggunakan data tentang Indeks Pembangunan Manusia Bangsa Indonesia dari tahun 1994-2013. Objek penelitian ini adalah pembahasan tentang pengaruh hubungan variabel pendidikan, konsumsi protein, konsumsi kalori, dan upah dengan indeks pembangunan manusia. Penarikan sampel dilakukan dengan menggunakan metode survei dengan teknik korelasional. Untuk mendapatkan data peneliti menggunakan data skunder tahun 1994-2013, nilai yang diambil dari Biro Pusat Statistik dengan menggunakan teknik dokumentasi. Hasil perhitungan persamaan akhir estimasi yaitu ?= 45,992 + 0,215 X1 + -0,264 X2 + 4,156 X3+ 0,321 X4. Koefisien desterminan sebesar 98,9 persen sisanya 1,1 persen karena pengaruh variabel lain. Ini artinya sumbangan variabel pendidikan, konsumsi protein, konsumsi kalori, dan upah terhadap peningkatan indeks pembangunan manusia sebesar 98,9 persen  dan sisanya 1,1 persen dari variabel bebas lainnya diluar model penelitian. Dari hasil penelitian diperoleh koefisien regresi yang paling kecil terhadap Indeks Pembangunan Manusia adalah variabel konsumsi protein sebesar -0,264. Maka dari itu diharapkan kepada Pemerintah Indonesia harus membuat kebijakan yang dapat memberikan hak yang layak bagi rakyat Indonesia agar dapat menikmati pangan yang bergizi seperti protein dan kalori.Kata kunci: Faktor Pendidikan, Gizi, Konsumsi Kalori, Upah, dan  Index Mutu Hidup (IMH/HDI)